PERANCANGAN FASILITAS PEMBINAAN DAN REKREASI TUNANETRA DENGAN PENDEKATAN INDERA - Evangelista Putri Herlambang; Mekar Sari Suteja (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
According to the Indonesian Ministry of Health, the blind population in Indonesia is estimated to be around 1.5% of the total Indonesian population, including those who are totally blind or have milder visual impairment. The Ministry of Women's Empowerment and Child Protection, explained that individuals with visual disabilities are those who have a visual clarity level of less than 6 per 60 after correction or have no visual ability at all. This significant amount is still not comparable to the provision of special facilities for the blind. Social discrimination is also experienced by blind people in Indonesia. In everyday life, children with visual impairments really need parental guidance and vice versa, parents who act as caregivers and intermediaries for children in the community must adapt to their child's condition. They need to learn a lot in assisting with special needs and monitoring the growth and development of their children. The design uses behavioral and narration methods through direct observation of the visually impaired which is very dependent on the senses of hearing and touch. The way the blind "see" is by hearing, tapping and touching. In addition, objects or furniture around become a way of finding for the blind. The design solution uses an empathetic architecture which is a key element of human-centred design. The design focuses on sensory design which is expected to help the blind to get to know their surroundings better and make it easier for them to move. Aspects of the building that are strengthened are lighting, texture, aroma, and location of space. This design accommodates the needs for mobility and sensory development for blind people aged 0-17 years and families with disabilities. Apart from that, it provides educational recreation for the public so they can empathize with the blind in a veiled and enjoyable way. Keywords:  blind; development; family; recreation; society Abstrak Menurut Kementerian Kesehatan RI, populasi tunanetra di Indonesia diperkirakan sekitar 1,5% dari keseluruhan penduduk Indonesia, termasuk mereka yang mengalami kebutaan total maupun gangguan penglihatan yang lebih ringan. Kementrian Pemberdayaan Perempuan dan Perlindungan Anak, menjelaskan bahwa individu dengan disabilitas penglihatan adalah mereka yang memiliki tingkat kejelasan penglihatan kurang dari 6 per 60 setelah koreksi atau tidak memiliki kemampuan penglihatan sama sekali. Jumlah yang signifikan ini ternyata masih belum sebanding dengan penyediaan fasilitas khusus bagi para tunanetra. Diskriminasi sosial juga dialami oleh penyandang tunanetra di Indonesia. Dalam kehidupan sehari-hari anak penyandang tunanetra sangat membutuhkan bimbingan orang tua dan sebaliknya orang tua yang berperan sebagai perawat dan perantara anak kepada masyarakat harus menyesuaikan kondisi anaknya. Mereka perlu banyak belajar dalam mendampingi kebutuhan khusus dan mengawasi tumbuh kembang anaknya. Perancangan menggunakan metode perilaku dan narasi melalui observasi langsung pada tunanetra sangat bergantung pada indera pendengar dan peraba. Cara tunanetra "melihat" adalah dengan mendengar, mengetuk dan meraba. Selain itu, benda atau perabot sekitar menjadi way of finding bagi tunanetra. Solusi desain menggunakan arsitektur empati yang merupakan suatu elemen utama dari desain yang berpusat pada manusia. Perancangan berfokus pada desain sensorik yang diharapkan dapat membantu tunanetra untuk lebih mengenal sekitar dan mempermudah mereka beraktivitas. Aspek bangunan yang diperkuat merupakan pencahayaan, tekstur, aroma, dan lokasi ruang. Perancangan ini mewadahi kebutuhan pembinaan mobilitas dan indera penyandang tunanetra usia 0-17 tahun dan keluarga penyandang. Selain itu memberikan rekreasi edukatif bagi masyarakat agar dapat berempati pada tunanetra dengan cara yang terselubung dan bisa dinikmati.